Morphometry of the glenoid cavity and its correlation with selected geometric measurements of the scapula (Bangladesh Journal of Medical Science, 2017)
Introduction: An understanding of the normal glenoid cavity morphometry is important in corroborating the basis of luxation at the glenohumeral joint (GHJ). This study was carried out to determine the morphomertic relationship of the glenoid cavity to joint stability and device models to estimateglenoid cavity dimensions ofthe scapular boneof Nigerian origin in a post-mortem skeletal state using selected angles and dimensionMethods: A total of 200wellmacerated unpaired scapulaebone (96 right and 104 left) with complete ossification were used for this study. Geometric measurements were taken using standard procedures. SPSS (IBM® version 20) was used to analyze the data and the results of all measured parameters (for both sides and total) were presented. Correlation was determined from the summation of the bilateral measurement of; the superior (SSA), inferior (ISA) and medial (SVA) angles of the scapulae, maximum height of the scapula (MHS), and maximum glenoid height and width (MGH and MGW). Glenoid index (GI) was calculated by dividing MGW by MGH. Regression formulae for estimation the glenoid cavity parameters were derived. Significance level was set at 95% (P?0.05 was considered significant).Result: The mean GIwas calculated as 68.18±5.93% (with min. and max. ratio of 54% and 87%respectively). Of the predictor variables for estimating MGH and MGW, SSA was weakly (-) correlated (r